Export, Migration, and Costs of Market Entry: Evidence from Central European Firms - Dieter Pennerstorfer (Austrian Institute of Economic Research (WIFO), 2011)
In this paper I analyse the export behaviour of firms located in different Central European countries (Austria, Hungary, Czech Republic and Slovakia) with respect to migration. Ever since the seminal article by Gould (1994) on immigrant links to their home country and due to empirical research following his contribution, it is a well established result that immigrants from a particular country spur exports to and imports from that destination. Chaney (2008) shows that a decrease in fixed costs of exporting increases the number of exporters (extensive margin), whereas a reduction in variable costs also increases the volume exported by each exporting firm (intensive margin). Empirical contributions using firm-level data focus on various aspects influencing costs of exporting (like spillover effects of nearby firms or financial factors), but leave out the issue of migration. I combine detailed information coming from a questionnaire conducted among 8,300 firms on the export behaviour to different countries with regional data on migration from the European Labour Force Survey (LFS). I find evidence that both the propensity to export and - to a much smaller extent - the volume of sales of exporting firms to a particular destination is higher for firms located in regions with a larger number of immigrants from that country. I conclude that migrants mainly reduce fixed costs of exporting.
Keywords: 330; Firm-level data; Export destinations; Immigrants; Margins of trade; Export; Markteintritt; Arbeitsmigranten; Vergleich; Österreich; Ungarn; Slowakei; Tschechien